Ein Konzept für die Kohlenstoffkreislaufwirtschaft Sektorkopplung zwischen Energie, Chemie & Abfall. Issue 1 (20th October 2017) - Meyer, Bernd; Keller, Florian; Wolfersdorf, Christian; Lee, Roh Pin
Abstract: A concept for a stepwise closure of the carbon cycle through a coupling of low emissions coal chemistry, waste management, and energy sectors via co‐gasification of coal and waste with the integration of renewably generated hydrogen is introduced. Goal is the achievement of zero CO2 emissions through an integration of renewable energy. Results from a case analysis of the required demand for renewable energy to achieve this goal for olefin production in Germany is presented. Findings show that the gasification route requires only about half the renewable energy to achieve zero CO2 emissions compared to other routes.